TGFβ in malignant canine mammary tumors: relation with angiogenesis, immunologic markers and prognostic role - Maria Isabel Carvalho; Ricardo Silva-Carvalho; Justina Prada; Carla Pinto; Hugo Gregório; Luis Lobo; Isabel Pires; Felisbina L. Queiroga (Veterinary Quarterly)
Transforming growth factor-β (TGFβ) and FoxP3 regulatory T cells (Treg) are involved in human breast carcinogenesis. This topic is not well documented in canine mammary tumors (CMT). In this work, the tumoral TGFβ expression was assessed by immunohistochemistry in 67 malignant CMT and its correlation to previously determined FoxP3, VEGF, and CD31 markers and other clinicopathologic parameters was evaluated. The high levels of TGFβ were statistically significantly associated with skin ulceration, tumor necrosis, high histological grade of malignancy (HGM), presence of neoplastic intravascular emboli and presence of lymph node metastases. The observed levels of TGFβ were positively correlated with intratumoral FoxP3 (strong correlation), VEGF (weak correlation) and CD31 (moderate correlation). Tumors that presented a concurrent high expression of TGFβ/FoxP3, TGFβ/VEGF, and TGFβ/CD31 markers were statistically significantly associated with parameters of tumor malignancy (high HGM, presence of vascular emboli and nodal metastasis). Additionally, shorter overall survival (OS) time was statistically significantly associated with tumors with an abundant TGFβ expression and with concurrent high expression of TGFβ/FoxP3, TGFβ/VEGF, and TGFβ/CD31. The presence of lymph node metastasis increased 11 times the risk of disease-related death, arising as an independent predictor of poor prognosis in the multivariable analysis. In conclusion, TGFβ and Treg cells seem involved in tumor progression emerging as potential therapeutic targets for future immunotherapy studies.